PENGARUH INFLASI, SUKU BUNGA, KURS USD, DAN KEDATANGAN WISATAWAN KE BALI TERHADAP EKSPOR WOOD HANDICRAFT - Abiba, I Putu Adis; Dewi, Made Heny Urmila; Wenegama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2019)
This research is located in Bali Province. This location was chosen because in Bali have handicrafts and arts businesses since Bali is a tourist destination that is visited by many foreign and domestic tourists. In addition, Bali contributes quite a lot to Indonesia. The object in this study is Wood Handicraft Export. This research was conducted using an associative paradigm. The method used is non-participant observation. The analysis technique used is the test of multiple linear regression analysis. The variables in this study are inflation, interest rates, US Dollar exchange rates, tourist arrivals and Wood Handicraft Exports. Based on the discussion of the results of the research that has been carried out, it can be concluded that, Simultaneously the variables of inflation, interest rates, US dollar exchange rates and tourist arrivals have a significant effect on the value of wood handicraft exports. Partially the inflation variable, the US dollar exchange rate, and the arrival of tourists have a significant positive effect. The interest rate variable has a negative and significant effect on the value of wood handicraft exports. Inflation is the dominant variable. Keywords: inflation, interest rates, dollar exchange rate, exports, handicraft